Bilateral atypical femoral fractures treated with compression hip screw and intramedullary nail fixation. (February 2022) - Kitajima, Masato; Takahashi, Tomoki; Takai, Hirokazu
Abstract: Atypical femoral fractures (AFF) are more difficult to treat than typical femoral fractures; they require strong fixation and good reduction. Intramedullary (IM) nailing is the first option for the treatment of complete AFF; however, there are few reports comparing IM nailing and extramedullary fixation. Moreover, there are no reports on the outcomes of bilateral atypical subtrochanteric femoral fractures treated with an IM nail on one side and a compression hip screw (CHS) on the other. We report the case of a 69-year-old woman who had been on risedronate sodium once a month since she was 58 years old. She reportedly felt pain in both her thighs due to an undiagnosed cause. Six months later, she fell and was diagnosed with bilateral complete atypical femoral subtrochanteric fractures (right side: Seinsheimer type IIC; left side: Seinsheimer type IIA). Four days later, she underwent CHS on the right side and IM nailing after open reduction surgery on the left. The reduction was successful. The left side healed 6 months after surgery, but the right side healed only after 14 months, despite assistance with low-intensity pulsed ultrasound. In atypical femoral subtrochanteric fractures, good reduction is important for healing, but, in this case, the CHS side healed slowly despite achievement of good reduction because of the difference in the fixation force between IM nailing and CHS, in addition to a probable occurrence of severely suppressed bone turnover (SSBT). Furthermore, reaming was not done on the CHS side, which may have contributed to the delay in bony union. IM nailing is the first option for atypical femoral subtrochanteric fractures because of faster union and lower reoperation rate than extramedullary fixation. Based on our findings, we recommend IM nailing as the first option for atypical femoral subtrochanteric fractures when good reduction can be achieved.